Role of Interleukin-17 in Acute Pancreatitis - Li, Guanqun; Chen, Hongze; Liu, Liwei; Xiao, Peng; Xie, Yu; Geng, Xinglong; Zhang, Tao; Zhang, Yang; Lu, Tianqi; Tan, Hongtao; Li, Le; Sun, Bei (Frontiers in Immunology, 2021)
Acute pancreatitis (AP) is a leading cause of death and commonly accompanied by systemic manifestations that are generally associated with a poor prognosis, making it a headache for clinicians. Many cytokines contribute to the damage of pancreatic tissue, also cause systemic injury. Interleukin-17 (IL-17) is a cytokine with potential effects in AP which plays a potential role. Specially, IL-17 has an important place in the immune response and cause interactions between different inflammatory mediators in AP-related microenvironment. In this literature review, the authors will discuss the existing academic understanding of IL-17 and the impacts of IL-17 in different cells(especially in acinar cell and immune system cells) in AP pathogenesis. The clinical significance and the mechanisms of IL-17 on AP deterioration are emphasized. The evidence suggests that inhibiting the IL-17 cytokine family could alleviate the pathogenic process of AP and accelerate the improvement or prevent the progression towards deterioration.